Effect of interpregnancy interval on outcomes of pregnancy after recurrent pregnancy loss. (September 2013) - Bentolila, Yaara; Ratzon, Ronit; Shoham-Vardi, Ilana; Serjienko, Ruslan; Mazor, Moshe; Bashiri, Asher
Abstract Objective: To examine the effect of interpregnancy interval (IPI) on outcomes of pregnancy after recurrent pregnancy loss (RPL). Methods: A retrospective cohort study including 325 patients treated at a RPL clinic, with two or more consecutive pregnancy losses followed by a subsequent (index) pregnancy, of whom 163 had IPI ≤ 6 months, and 212 had IPI > 6 months. Results: Pregnancy loss rate in the index pregnancy was positively associated with increased IPI (18.6% in women with IPI ≤ 6 months, and 29.7% in women with IPI > 6 months; p = 0.029). In a multivariable logistic analysis, excluding women with fertility problems, and adjusting for maternal age and ethnicity, the OR for pregnancy loss rate for IPI longer than 6 months compared to shorter IPI was 1.76 (95%CI: 0.96–3.22, p = 0.067). Conclusions: Our results suggest that IPI shorter than 6 months, in women with no fertility problems, is associated with lower rate of subsequent miscarriage. Further studies are needed to substantiate this finding.